Lactobacillus helveticus (ATCC 27558) upregulates Runx2 and Bmp2 and modulates bone mineral density in ovariectomy-induced bone loss rats - Parvaneh, Maria; Karimi, Golgis; Jamaluddin, Rosita; Ng, Angela Min Hwei; Ibrahim, Zuriati; Muhammad, Sani Ismaila (Dove Medical Press, 2018)
Purpose: Osteoporosis is one of the major health concerns among the elderly population, especially in postmenopausal women. Many menopausal women over 50 years of age lose their bone density and suffer bone fractures. In addition, many mortality and morbidity cases among the elderly are related to hip fracture. This study aims to investigate the effect of Lactobacillus helveticus (L. helveticus) on bone health status among ovariectomized (OVX) bone loss-induced rats. Methods: The rats were either OVX or sham OVX (sham), then were randomly assigned into three groups, G1: sham, G2: OVX and G3: OVX+L. helveticus (1 mL of 10 8 –10 9 colony forming units). The supplementation was force-fed to the rats once a day for 16 weeks while control groups were force-fed with demineralized water. Results: L. helveticus upregulated the expression of Runx2 and Bmp2, increased serum osteocalcin, bone volume/total volume and trabecular thickness, and decreased serum C-terminal telopeptide and total porosity percentage. It also altered bone microstructure, as a result increasing bone mineral density and bone strength. Conclusion: Our results indicate that L. helveticus attenuates bone remodeling and consequently improves bone health in OVX rats by increasing bone formation along with bone resorption reduction. This study suggests a potential therapeutic effect of L. helveticus (ATCC 27558) on postmenopausal osteoporosis